Non-Toxic Buffer Layers in Flexible Cu(In,Ga)Se2 Photovoltaic Cell Applications with Optimized Absorber Thickness - Md. Asaduzzaman; Md. Billal Hosen; Md. Karamot Ali; Ali Newaz Bahar (International Journal of Photoenergy, 2017)
Absorber layer thickness gradient in Cu(In1−xGax)Se2 (CIGS) based solar cells and several substitutes for typical cadmium sulfide (CdS) buffer layers, such as ZnS, ZnO, ZnS(O,OH), Zn1−xSnxOy (ZTO), ZnSe, and In2S3, have been analyzed by a device emulation program and tool (ADEPT 2.1) to determine optimum efficiency. As a reference type, the CIGS cell with CdS buffer provides a theoretical efficiency of 23.23% when the optimum absorber layer thickness was determined as 1.6 μm. It is also observed that this highly efficient CIGS cell would have an absorber layer thickness between 1 μm and 2 μm whereas the optimum buffer layer thickness would be within the range of 0.04–0.06 μm. Among all the cells with various buffer layers, the best energy conversion efficiency of 24.62% has been achieved for the ZnO buffer layer based cell. The simulation results with ZnS and ZnO based buffer layer materials instead of using CdS indicate that the cell performance would be better than that of the CdS buffer layer based cell. Although the cells with ZnS(O,OH), ZTO, ZnSe, and In2S3 buffer layers provide slightly lower efficiencies than that of the CdS buffer based cell, the use of these materials would not be deleterious for the environment because of their non-carcinogenic and non-toxic nature.